Extracorporeal membrane oxygenation for COVID‐19: An evolving experience through multiple waves. Issue 11 (20th August 2022) - Smith, Nathan J.; Park, Sarah; Zundel, M. Tracy; Dong, Huaying; Szabo, Aniko; Cain, Michael T.; Durham, Lucian A.
Abstract: Background: Extracorporeal membrane oxygenation (ECMO) has shown variable results in COVID‐19 pneumonia however, some evidence supports benefit. Here we compare our institution's ECMO outcomes across multiple waves of the COVID‐19 pandemic. Methods: All patients who received ECMO for COVID‐19 between March 1, 2020, and March 1, 2021, were reviewed. Patients received venovenous (VV) or right ventricular assist device (RVAD/ECMO) ECMO. Early (March 1–July 6, 2020, Era 1) and late (July 7, 2020–March 1, 2021, Era 2) pandemic RVAD/ECMO patients were compared. Results: Fifty‐four patients received ECMO of which 16 (29.6%) patients received VV ECMO and 38 (70.4%) RVAD/ECMO. Median age was 53.0 years, body mass index 36.1 kg/m 2, 41.2% female, and 49% Caucasian. The most common pre‐cannulation treatments included steroids (79.6%) and convalescent plasma (70.4%). Median time from admission to cannulation was 7.0 days. Median support time was 30.5 days (VV ECMO 35.0 days, RVAD/ECMO 26.0 days). In‐ hospital mortality was 42.6% (39.5% RVAD/ECMO, 50.0% VV ECMO). Significant morbidities included infection (80.8%), bleeding events (74.5%), and renal replacement therapy (30.8%). Cumulative mortality 120‐days post‐cannulation was 45.7% (VV ECMO 60.8%, RVAD/ECMO 40.0%). RVAD/ECMO Era 1 demonstrated a significantly lower cumulative mortality (16.2%) compared to Era 2 (60.4%). Competing risk analysis found age (HR 0.95, [95% CI 0.92, 0.98] p = 0.005) to be a protective factor for survival. Conclusion: ECMO support for COVID‐19 is beneficial but carries significant morbidity. RVAD/ECMO support demonstrated consistent advantages in survival to VV‐ECMO, but with declining efficacy across time during the COVID‐19 pandemic. Abstract : Outcomes for ECMO for COVID‐19 through multiple waves of the pandemic.